Cytokine levels as predictors of mortality in critically ill patients with severe COVID-19 pneumonia: Case-control study nested within a cohort in Colombia - Molina, Francisco José; Botero, Luz Elena; Isaza, Juan Pablo; Cano, Luz Elena; López, Lucelly; Hoyos, Lina Marcela; Correa, Elizabeth; Torres, Antoni (Frontiers in Medicine, 2022)
Background: High levels of different cytokines have been associated in COVID-19 as predictors of mortality; however, not all studies have found this association and its role to cause multi-organ failure and death has not been fully defined. This study aimed to investigate the association of the levels of 10 cytokines with mortality in patients with COVID-19 admitted to the intensive care unit (ICU). Methods: This is a case-control study nested within a cohort of patients with COVID-19 who were on mechanical ventilation and were not hospitalized for more than 48 hours across nine ICUs in Medellín, Colombia. Serum samples were collected upon admission to the ICU and seven days later and used to measure cytokine levels. Results: Upon admission, no differences in mortality between the cytokine levels were observed when comparisons were made quantitatively. However, in the multivariate analysis, patients with median IL-1β levels < 1.365 pg/mL showed an increase in mortality (OR = 3.1; 1.24‒7.71; p = 0.015). On day 7 in the ICU, IL-1β median levels were lower (0.34 vs. 2.41 pg/mL, p = 0.042) and IL-10 higher (2.08 vs. 1.05 pg/mL, p = 0.009) in patients who died. However, in the multivariate analysis, only IL-12p70 was associated with mortality (OR = 0.23; 0.07‒0.73; p = 0.012). The mean difference in the levels between day 1 and day 7 decreased in both IFN-γ (3.939 pg/mL, p < 0.039) and in IL-18 (16.312 pg/mL, p < 0.014) in the patients who died. A low IL-1β/IL-10 ratio was associated with mortality on both day 1 and day 7, while an IL-1β/IL-10 ratio below the cut-off on day 7 was associated with decreased survival. The lowest TNFα/IL-10 ratio was associated with mortality only on day 7. Conclusions: At the time of admission, patients with median IL-1β levels lower than 1.365 pg/mL had increased mortality. An IL-1β/IL-10 ratio < 2 at day 7 and IL-12p70 levels > 1.666 pg/mL was associated with decreased survival.